Factors That Influence The Numbers of Children in The Village Pusong Banda Sakti Lhokseumawe City - Mursyida, Rika; Mutiara, Erna; Asfriyati, Asfriyati (Universitas Ubudiyah Indonesia, 2018)
The number of children means how many children owned by someone, usually in the form of the intended family size. Family size will be increased, along with the increase in the number of children because each family attempts to get the number of children by their own way. The objective of the research was to find out some factors influenced the number of children such as the factors of motherâs age, family income, and child value through the first age at exposure to sexual intercourse at Pusong Village, Banda Sakti Subdistrict, City of Lhokseumawe, in 2017. The research was observational with cross sectional design. The population was 246 wives of PUS (Fertile Age Couple) at Pusong Village, in January, 2017, and 95 of them were used as the samples, using simple random sampling technique. The data were analyzed by using path analysis. The result of the research showed that simultaneously wifeâs age, family income, child value, and the first age at exposure to sexual intercourse influenced the number of children of 24.9%. Of the three independent variables, the variable of the first age at exposure to sexual intercourse influenced the number of children (Ï < 0.001) with the amount of influence was 24.9%, and the rest (75.1%) was influenced by other factors such as Family Planning, education, and motherâs job. It is recommended that community and religious leader at Pusong Village, as the head of âtuha peut gampongâ should correct negative perception about the use of contraception device so that the community will believe that contraception device is halal (legitimate) and can be used by the wives of fertile age couple arranging their number of children.Â Keywords: wifeâs age, family income, child value, the first age at exposure to sexual intercourse, number of children